2015
DOI: 10.4093/dmj.2015.39.4.307
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Management in Type 2 Diabetes Mellitus at General Hospitals in South Korea

Abstract: BackgroundIn Korea, the prevalence, complications, and mortality rate of diabetes are rapidly increasing. However, investigations on the actual condition of diabetes management are very limited due to lack of nation-wide research or multicenter study. Hence, we have minutely inquired the current status of diabetes management and achievement of glucose target goal in general hospital offering education program. That way, we are able to furnish data for policy making of diabetes education and draw up guideline w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
10
2
1
Order By: Relevance
“…The increase could be associated with the scale-up of comprehensive treatment and self-management of diabetes in China in recent years. However, the control rate in this study was still lower than the results reported in Korea, USA, European countries, and Japan [ 19 , 20 ]. These findings show that although MNT has been applied in China for about 5 years, the knowledge and practice of MNT in diabetes patients in urban China are still suboptimal, and the controlling rate of blood glucose is still very low.…”
Section: Discussioncontrasting
confidence: 91%
“…The increase could be associated with the scale-up of comprehensive treatment and self-management of diabetes in China in recent years. However, the control rate in this study was still lower than the results reported in Korea, USA, European countries, and Japan [ 19 , 20 ]. These findings show that although MNT has been applied in China for about 5 years, the knowledge and practice of MNT in diabetes patients in urban China are still suboptimal, and the controlling rate of blood glucose is still very low.…”
Section: Discussioncontrasting
confidence: 91%
“…Thus, a relatively large number of patients with type 2 diabetes are exposed to the risks of CVD [13]. …”
Section: Introductionmentioning
confidence: 99%
“…The American Diabetes Association recommends that self-management skills and diabetes knowledge be assessed at least annually and encourages continuing diabetes education [10]. Nonetheless, a recent study revealed that the participation rate in diabetes education programs was only 53% in Korea [11]. …”
Section: Introductionmentioning
confidence: 99%